ALGORITHMS TO IDENTIFY TRUST AMONG FRIENDS ON SOCIAL NETWORKING SITES BASED ON ONTOLOGY - Phạm Thị Thu Thúy (Tạp chí Khoa học Đại học Đà Lạt)
Nowadays, along with the development of Information Technology (IT), more and more people use social networking sites, especially Facebook, to build and expand their relationships. However, with the diversity and abundance of users, the credibility of friends on Facebook is of great concern to many users. This article aims to measure reliability (trust) by using user interactions on Facebook including likes, comments, and friends' tags on users’ photos and posts. This paper synthesizes and analyzes common reliability formulas and presents a reliability algorithm.